Assessing the expression of differentiation antagonizing non-protein coding RNA (DANCR) in newly diagnosed Egyptian acute myeloid leukemia patients - Nour Mohammed Rasheed; Howaida Attia Nounou; Soad Mohamed Eltabakh; Nahla A. M. Hamed; Ayman Ahmed Darwish (SpringerOpen, 2023)
Abstract Background Role of Long non-coding RNAs in cancer research in the recent years have been highlighted with evidence to their involvement in cancer disease pathogenesis and progression. One of these emerging long non-coding RNAs is differentiation antagonizing non-protein coding RNA (DANCR). DANCR distinct expression in different cancers and implication in tumor signaling pathways made it a promising therapeutic target for cancer. The purpose of this study was to evaluate DANCR expression in de novo acute myeloid leukemia (AML) patients and to assess DANCR expression in relation to cytogenetics and French American British (FAB) AML classification as well as correlate DANCR expression with patients' response to treatment. The present study included 60 newly diagnosed AML patients and 30 healthy subjects as controls. Relative DANCR expression was done using real time qPCR method. Results DANCR was significantly downregulated in AML patients compared to controls (p = 0.038). In addition, DANCR showed significantly lower expression in M4 and M5 compared to M0, M1, and M2 groups (p < 0.001). Furthermore, DANCR expression was significantly downregulated in cytogenetically normal AML patients compared to the controls (p = 0.011). Conclusion Significant downregulation of DANCR in AML suggests a potential tumor suppressor role and variable expression of DANCR among AML subtypes suggests that DANCR action may be different among AML subtypes. Also, M1 subtype patients with higher DANCR expression were less refractory to treatment and therefore less resistant to cytarabine.